PENGUKURAN KEBERHASILAN DIKLAT MELALUI MODEL EVALUASI KIRKPATRICK - Ai Nurjanah (Tatar Pasundan: Jurnal Diklat Keagamaan, 2018)
This article discusses quantitative research through descriptive method of case study at offcampus PKG training and PKB Aliyah madrasah teacher in Kanmenag Cirebon City. This research is to measure the success of the training through the kirkpatric evaluation model. Evaluation was conducted in 4 stages; Measurement of the success of the training by applying the kirkpatrick evaluation model through four stages. Assessment stage 1: reaction level using the participants' assessment questionnaire on the implementation of training and assessment of widyaiswara. Assessment of participants on the implementation of training average of 85.98 and the assessment of the participants against the widyaiswara of 87.78. Phase 2, the level of learning measurement of training participants includes three aspects, knowledge, skills and attitudes. The average pretest score was 43 and the highest score was 77, the average score of postes 81. The average of pretest and posttest results increased by 65. The average score of the product was 91.66 and the attitude was 88.66. Of the 3 aspects assessed the average score of 80 over the criteria of at least 76.00, then it can be said at this level works well. Phase 3, the quantitative level of behavior average score of the 4 aspects of 3.7. Indicating at this level changes behavior well. While in stage 4 the result level (result level) obtained an average score of 3.8 indicating alumni diklat can improve his career as the impact of training results.  Key words:The success rate of the training, the evaluation model of kirkpatrick.